Early child care and maternal employment: empirical evidence from Germany - Franziska Zimmert (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper examines the effect of an expansion of subsidized early child care on maternal labor market outcomes. It contributes to the literature by analyzing, apart from the employment rate and agreed working hours, preferred working hours. Semi-parametric difference-in-differences estimation based on survey data from the German Micro Census results in positive effects on the employment rate, as well as on agreed and preferred working hours. As agreed and preferred working hours adjust in line with each other, expansion of early child care can tap labour market potentials beyond those of currently underemployed mothers. Moreover, conditional effects show that especially better educated and non-single mothers respond to the reform.
Keywords: J21; J22; 330; early child care; maternal labor supply; semi-parametric difference-in-differences; subsidized child care; working hour preferences